Correlations between the sequelae of stroke and physical activity in Korean adult stroke patients - Kim, Ki-Jong; Kim, Hwang-Yong; Chun, In-Ae (Journal of Physical Therapy Science, 2016)
[Purpose] The present study investigated a wide range of stroke patients living in South Korea using the Korean Community Health Survey raw data to determine the correlation between stroke and physical activity. [Subjects and Methods] This study used raw data from the 2012 Korean Community Health Survey. The total number of participants was 228,921; of the 4,475 stroke patients who had been diagnosed by a medical doctor or an oriental medical doctor, the data for 4,460 patients, excluding 15 whose amount of physical activity was unclear, were used in the analysis. [Results] The amount of physical activity performed by patients who had sequelae was significantly lower than that performed by patients who no longer had sequelae. Similarly, for the type of sequelae, palsy in the arms and legs, facial palsy, communication disability, swallowing or eating disability, and visual disability were associated with lower physical activity. Furthermore, as the number of sequelae increased, patients performed significantly less physical activity. [Conclusion] The findings suggest that when decisions on national policies and budgets are made, methods for increasing the physical activity of patients with a history of stroke should be considered.